Pemberdayaan Kelompok Tani Kopi untuk Memproduksi Kopi Toraja Bubuk di Kabupaten Tana Toraja - Rosalia Sira Sarungallo; Denny Denny; Kordiana Sambara (DEDIKASI, 2018)
The purpose of this activity was to improve the quality of the powdered Toraja coffee and the income ofthe people in the Dewata Village. Through this activity, the community in Dewata Village was empowered toincrease their knowledge through training in producing quality powdered Toraja coffee. The training programincluded how to produce powdered Toraja coffee production that has a good quality, ranging from coffee beanroasting process, sieving powdered Toraja coffee and coffee packaging. In addition, lectures were held to increasepublic knowledge about group management and marketing of powdered Toraja coffee that has been produced. Theresults of the activities carried out in the Dewata Village were products of flavored powdered Toraja coffee andtypical toraja aroma with a more attractive packaging.